Advanced Nurse Practitioner (ANPs) experiences of the Quality and Outcomes Framework (QOF) Scheme: a UK case study (BMJ Open)
Objectives The primary focus of pay-for-performance (P4P) schemes in the UK has traditionally been related to the public health and inclusion elements related to the activities of doctors with comparatively less attention given to nursing care as a component of the scheme. However, nursing is an integral part of healthcare delivery in the National Health Service and nurses constitute the major group of healthcare professionals in most countries. Our aim was to explore advanced nurse practitioner (ANPs) experiences of the Quality and Outcomes Framework (QOF), using the Implicit Leadership Theory (ILT) frame.Methods We used a case study approach. Six articles on the QOF work were synthesised, focused on ANPs and their leadership potential in healthcare. Evidence showed that despite having importance in delivering the activities of QOF, nursing activities overlooked. We undertook a thematic synthesis of these papers, with a specific focus ANPs’ leadership development in Long Term Conditions (LTC) care within general practice and capacity to influence the healthcare system.Findings Six themes were identified: (1) sensitivity, patient-centred care, context and continuity of care; (2) intelligence—leaders capable of making strategic decisions in healthcare settings, (3) dedication, trust, equity and equality, (4) dynamism of nursing, (5) tyranny, guise of teamwork, collaboration and (6) nursing and healthcare leadership.Conclusions Nurses in leadership roles created good working relationships, coped with conflicts and contributed to shared objectives and were sympathetic collaborators. Using the six ILT characteristics, we found that nurses were collaborators. Future P4P schemes should benefit from a collective lens of healthcare personnel when focusing on quality initiatives and improving the delivery of healthcare activities.